Interhospital Transport on Extracorporeal Membrane Oxygenation of Neonates—Perspective for the Future - Broman, Lars Mikael (Frontiers in Pediatrics, 2019)
In recent years the number of extracorporeal membrane oxygenation (ECMO) cases in neonates has been relatively constant. Future expansion lays in new indications for treatment. Regionalization to high-volume ECMO centers allows for optimal utilization of resources, reduction in costs, morbidity and mortality. Mobile ECMO services available “24-7” are needed to provide effective logistics and reliable infrastructure for patient safety. ECMO transports are usually high-risk and complex. To reduce complications during ECMO transport communication using time-out, checklists and ECMO A-B-C are paramount in any size mobile program. Team members’ education, clinical training and experience are important. For continuing education, regular wet-lab training and simulation practices in teams increase performance and confidence. In the future the artificial placenta for the extremely premature infant (23-28 gestational weeks) will be introduced. This will enforce the development and adaptation of ECMO devices and materials for increased biocompatibility to manage the high-risk prem-ECMO (28-34 weeks) patients. These methods will likely first be introduced at a few high-volume neonatal ECMO centers. The ECMO team brings bedside competence for assessment, cannulation and commencement of therapy, followed by a safe transport to an experienced ECMO center. How transport algorithms for the artificial placentae will affect mobile ECMO is unclear. ECMO transport services in the newborn should firstly be an out-reach service led and provided by ELSO member centers that continuously report transport data to an expansion of the ELSO Registry to include transport quality follow-up and research. For future development and improvement follow-up and sharing of data are important.